Descriptive Study on the Circumstances concerning Confirmation of Contraindications and Careful Administration upon Purchasing Over-the-Counter Cold Medication and Manifestation of After-use Urinary Disorders - SASAKI, Keiko; YAMAMOTO, Toshinori; OHBAYASHI, Masayuki; KOHYAMA, Noriko; KOBAYASHI, Yasuna (YAKUGAKU ZASSHI, 2008)
Over-the-counter medications are primarily for self-medication, where the seller, such as a pharmacist, provides the necessary information and the consumer uses the medication at his or her own discretion based on the information provided. A Web survey was conducted from February 8 to 13, 2006, involving 500 men and women, ranging in age from 50 to 69 years, who had purchased over-the-counter medications for the common cold within the past 3 years. Upon consultation with and purchase of a cold medication from a pharmacist, 84.2% of respondents reported “being asked my symptoms,” and less frequently (12.3-21.3%) being asked about contraindications/careful administration. Most respondents (60.8%) when asked whether they confirmed “contraindications/careful administration” responded negatively, stating they “occasionally do not confirm” or “do not confirm.” In addition, among men aged 50-69 years, it became clear that 6.0% had experienced aggravation of prostatic hypertrophy symptoms after taking a cold medication. It is assumed that symptoms are usually confirmed upon the sale of over-the-counter medications, but the rate of confirming whether the consumer may need to consider contraindications/careful administration is low. Urinary retention is a preventable side effect because the confirmation prior to taking the medication can be made. Accordingly, some of those side effects can be avoided by ensuring the environment for confirming whether the individual corresponds to “contraindications/careful administration” before taking the medication.